SMRT corepressor interacts with PLZF and with the PML-retinoic acid receptor α (RARα) and PLZF-RARα oncoproteins associated with acute promyelocytic leukemia - Hong, Suk-Hyun (The National Academy of Sciences of the USA, 1997)
Retinoic acid receptors (RARs) are hormone-regulated transcription factors that control key aspects of normal differentiation. Aberrant RAR activity may be a causal factor in neoplasia. Human acute promyelocytic leukemia, for example, is tightly linked to chromosomal translocations that fuse novel amino acid sequences (denoted PML, PLZF, and NPM) to the DNA-binding and hormone-binding domains of RARα. The resulting chimeric receptors have unique transcriptional properties that may contribute to leukemogenesis. Normal RARs repress gene transcription by associating with ancillary factors denoted corepressors (also referred to as SMRT, N-CoR, TRAC, or RIP13). We report here that the PML-RARα and PLZF-RARα oncoproteins retain the ability of RARα to associate with corepressors, and that this corepressor association correlates with certain aspects of the leukemic phenotype. Unexpectedly, the PLZF moiety itself can interact with SMRT corepressor. This interaction with corepressor is mediated, in part, by a POZ motif within PLZF. Given the presence of POZ motifs in a number of known transcriptional repressors, similar interactions with SMRT may play a role in transcriptional silencing by a variety of both receptor and nonreceptor transcription factors.